Analysis of Odor and Color Parameters in the Meat Freshness Detection System Using Gas Sensor and Reaction Kinetics Methods - Erlina Nur Arifani; Sevia Indah Purnama; Mas Aly Afandy; Danny Kurnianto Kurnianto; Nurul Latifasari Latifasari (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
The degradation of beef is typically indicated by the presence of NH3 as ammonia and H2S as hydrogen sulfide. The NH3 and H2S level will increase in line with the meat spoilage. This research is aims to develop the new meat storage with NH3 and H2S level measurement to detect spoilage in beef. This measurement is needed to make sure the meat that are store is still in good condition or already spoil. Kinetic model of NH3 and H2S gas is used to determine the correlation between meat spoilage with time. This equipment has main parts that consist of sensor system microcontroller and computer. The MQ 137 works as detector of NH3 gas which are emitted by sample of beefs during observation. The MQ – 136 sensor works as detector of H2S gas. This research also analyzes the color change in beef spoilage. The data of meat storage develop in this research shows that it can properly measure NH3 and H2S gases that occur during the gas evolution process. The color of the meat also changes while the meat spoilage starts. The rate constants of change of H2S and NH3 follow the zero-order kinetics of H2S and NH3 with constant rates of 0.90 and 0.95, respectively. This result shows that time highly correlated with the spoilage meat.